The most comprehensive history of fire activity in the Pur-Taz interfluve over the last 11,000 years (Western Siberia, Russia) - Nikita V. Shefer; Sergey V. Loiko; Ivan V. Kriсkov; Artem G. Lim (Acta Biologica Sibirica)
Climate change in the Arctic may increase the incidence of tundra fires, which is expected to significantly transform tundra ecosystems. Therefore, it is promising to study the tundra paleofire data to assess whether the projected increase in fire numbers is unique. In this study, we used five types of ancient fire proxies to estimate the number of fire events during the Holocene in the southern tundra of Western Siberia. Our integrated analysis of soil and peat deposit proxies allowed us to distinguish, for the first time, three different fire activity periods for this region. In the first period from 11.2 to 7.5 cal kyr BP, high fire activity was recorded. In the second period from 7.5 to 3.5 cal kyr BP the number of fire events is minimal. In the third period from 3.5 cal kyr BP to the present day, the number of pyrogenic events is maximum, and the maximum occurs in the second and third millennia from our days. For the third period, a temporal relationship between fire frequency and archaeological cultures is noted. It was also established that in the second half of the Holocene in the southern tundra peat accumulation was not interrupted in fens permafrost polygonal peat plateaus. This allowed us to obtain a good time resolution of the peat charcoal record for the last 3.5 thousand years. Thus, this study demonstrates the occurrence of landscape fires in the southern tundra throughout the Holocene. And the predicted increase in the frequency of tundra fires has paleoecological analogues.